Clinical and pharmacological hallmarks of rifapentine’s use in diabetes patients with active and latent tuberculosis: do we know enough? - Zheng C; Hu X; Zhao L; Hu M; Gao F (Dove Medical Press, 2017)
Chunlan Zheng,1,* Xiufen Hu,2,* Li Zhao,1 Minhui Hu,1 Feng Gao3 1Department of Internal Medicine – Section 5, Wuhan Pulmonary Hospital (Wuhan Tuberculosis Control Institute), 2Department of Paediatrics, Tongji Hospital, 3Department of Endocrinology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China *These authors contributed equally to this work Abstract: Rifapentine is a rifamycin derivate approved by the US Food and Drug Administration in 1998 for the treatment of active, drug-susceptible tuberculosis (TB). In 2014, rifapentine was approved for the treatment of latent TB infection in patients at high risk of progression to active disease and is currently under evaluation by the European Medicines Agency. Expanding indications of rifapentine largely affect diabetes patients, since about one-third of them harbor latent TB. Clinical consequences of rifapentine use in this population and potentially harmful interactions with hypoglycemic agents are widely underexplored and generally considered similar to the ones of rifampicin. Indeed, rifapentine too may decrease blood levels of many oral antidiabetics and compete with them for protein-binding sites and/or transporters. However, the two drugs differ in protein-binding degree, the magnitude of cytochrome P450 induction and auto-induction, the degree of renal elimination, and so on. Rifapentine seems to be more suitable for use in diabetes patients with renal impairment, owing to the fact that it does not cause renal toxicity, and it is eliminated via kidneys in smaller proportions than rifampicin. On the other hand, there are no data related to rifapentine use in patients >65 years, and hypoalbuminemia associated with diabetic kidney disease may affect a free fraction of rifapentine to a greater extent than that of rifampicin. Until more pharmacokinetic information and information on the safety of rifapentine use in diabetic patients and drug–drug interactions are available, diabetes in TB patients treated with rifapentine should be managed with insulin analogs, and glucose and rifapentine plasma levels should be closely monitored. Keywords: rifamycin, antituberculosis treatment, glucose intolerance, hyperglycemia, safety